The law on the illicit enrichment crime and financial disclosure in Jordan: issue of effectiveness and enforceability - Abu-Morad, Mohannad Ahmad; Ayub, Zainal Amin; Mohd Noor, Fauziah (Academic Research Publishing Group, 2016)
Traditional prosecution of corruption proved useless results, due to futility of proving methods and the secretive nature of corruption case.Therefore, the financial disclosure system had been created to be an important and effective tool to curb corruption through prevention of conflict of interests and prosecution of illicit enrichment.Jordan adopted this system within the Illicit Enrichment Law aiming to prosecute illicit enrichment and deprive perpetrators and their accomplices from the proceeds of corruption. However, there are several problems inherent in the law that frustrates its objectives.Hence, this article discusses one of these issues, which is the relationship between the criminal liability of illicit enrichment and the obligation of submission the financial disclosure in accordance with the Jordan law, with some reference to the international standards.